2018
DOI: 10.1371/journal.pone.0200384
|View full text |Cite
|
Sign up to set email alerts
|

Prospective study of canine leptospirosis in shelter and stray dog populations: Identification of chronic carriers and different Leptospira species infecting dogs

Abstract: Dogs are highly susceptible to the leptospiral infection, notably stray and sheltered dogs. Unsanitary conditions often observed in dog shelters may predispose the introduction and spread of leptospires among sheltered populations, potentially increasing the chances for the inadvertent adoption of asymptomatically infected animals. The present work describes a longitudinal study using a multidisciplinary approach for the identification of chronically infected dogs and the characterization of potentially pathog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
52
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(60 citation statements)
references
References 74 publications
(96 reference statements)
2
52
1
3
Order By: Relevance
“…isolates were recovered from whole blood (n = 3), urine (n = 7) and abdominal effusion (n = 1) samples. Comparing with previous studies, leptospires were successfully recovered only from urine sample of the diseased dogs [46], shelter and stray dogs [47] and farm dogs [20]. This supports that urine samples are superior samples for leptospiral isolation in dogs regardless of the target population.…”
Section: Discussionsupporting
confidence: 72%
“…isolates were recovered from whole blood (n = 3), urine (n = 7) and abdominal effusion (n = 1) samples. Comparing with previous studies, leptospires were successfully recovered only from urine sample of the diseased dogs [46], shelter and stray dogs [47] and farm dogs [20]. This supports that urine samples are superior samples for leptospiral isolation in dogs regardless of the target population.…”
Section: Discussionsupporting
confidence: 72%
“…In the present study, 13.1% of 219 tested apparently healthy dogs had leptospiral DNA in their urine indicating shedder status of these animals. Previous studies have shown that clinically normal dogs can chronically shed leptospires in urine, contaminating the surroundings and potentially exposing other animals and people in that environment to infection [20,21,22,23]. Identification of urinary shedders is thus important in preventing spread of leptospirosis.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, "dog ownership" was identified as a potential risk factor for humans [17][18][19][20][21][22]. Worldwide studies showed a prevalence of urinary shedding of Leptospira in dogs between 0.2 and 31.1% by PCR [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37]. Shedding can also occur in healthy dogs [23, 25, 31-33, 35, 37].…”
Section: Introductionmentioning
confidence: 99%